Determinants of Stunting Incidents in Dolok Tolong Village, Sumbul District, Dairi Regency in 2022 - Evanata Lina Sinaga; Kesaktian Manurung; Taruli Rohana Sinaga (SEAN Institute, 2023)
Stunting is one of the problems currently being faced by Indonesia. Stunting is a problem of malnutrition caused by a lack of adequate intake over a long period of time which will cause difficulties in achieving optimal physical and cognitive development in the future, which is indicated by the value z-score Height/Length by Age less than -2SD. The incidence of stunting is influenced by various factors, namely history of exclusive breastfeeding, family income, maternal education, maternal height and parity. The general objective of this research is to determine the determinants of stunting events in Dolok Tolong Village, Sumbul District, Dairi Regency in 2022. The type of research used is observational comparative study research, the research method is a survey with a case control approach where research is carried out by comparing two groups of cases. and control group. The population in this study were all mothers who had toddlers who were not stunted and experienced stunting in Dolok Tolong Village. The population of children under five who are stunted is 67 people and 67 people who are not stunted. Based on the research results, it was found that there was a relationship between a history of exclusive breastfeeding and stunting (ρ-value = 0.000), there was a relationship between family income and stunting (ρ-value = 0.001), there was a relationship between maternal education and stunting (ρ-value = 0.029), there was a relationship between parity and stunting (ρ-value = 0.000), there was a relationship between maternal height and stunting (ρ-value = 0.000). The factor most associated with stunting in this study was maternal height, with Ods Ratio=5.9762. There is a need to increase health promotion and education to the public about the importance of good parenting patterns and fulfilling nutrition, especially in the first 1000 days of life, starting from when mothers are pregnant until children are 2 years old. Interventions during the first 1000 days of life are urgently needed to prevent stunting as a result of the intergenerational cycle of malnutrition.